Natural factors regulating mustard aphid dynamics in cabbage. Issue 3 (5th July 2018) - Fidelis, E.G.; Farias, E.S.; Silva, R.S.; Lopes, M.C.; Silva, N.R.; Picanço, M.C.
Abstract: Lipaphis erysimi (L.) Kaltenbach (Hemiptera: Aphididae) is one of the most important pests of brassica crops, mainly causing losses due to sap sucking, toxin injection and viral transmission. Knowledge about the main natural factors that regulate populations of this pest, as well as its critical mortality stage, is crucial for the development of integrated pest management of L. erysimi . Here, we determined the critical stage and key mortality factors for L. erysimi in cabbage using an ecological life table. Causes of mortality at each stage of L. erysimi development were monitored daily in the field for seven seasons. From the experimental data, we determined the key factor and critical stage of mortality through correlation and regression analyses. The nymphal stage, especially first instar nymphs, was critical for L. erysimi mortality. The key mortality factors were, in descending order of importance, physiological disturbances and predation by Syrphidae, Coccinellidae and Solenopsis ants. Therefore, control measures should target early stages of L. erysimi and the use of cabbage cultivars that have negative effects against L. erysimi may be a promising strategy for its management. Our results may be useful for plant geneticists who could develop new cabbage cultivars based on these findings. In addition, conservation measures of the main predators of L. erysimi may contribute to the natural control of this pest.